Нейрофизиологическое обоснование некоторой неврологической симтоматики острого периода черепно-мозговой травмы, обусловленной действием взрывной волны = Neurophysiological justification of some neurological symptoms of acute period of a craniocerebral injuries from an explosive waves - V. A. Коrshnyak; A. I. Gozhenko; B. A. Nаsibullin; Uy. V. Bowt; W. Zukow (Kazimierz Wielki University, 2016)
Коrshnyak V. А., Gоzhеnkо А. I., Nаsibullin B. А., Bоwt Uy. V., Zukow W. Нейрофизиологическое обоснование некоторой неврологической симтоматики острого периода черепно-мозговой травмы, обусловленной действием взрывной волны = Neurophysiological justification of some neurological symptoms of acute period of a craniocerebral injuries from an explosive waves. Journal of Education, Health and Sport. 2016;6(3):140-147. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.47947 http://ojs.ukw.edu.pl/index.php/johs/article/view/3430 https://pbn.nauka.gov.pl/works/721362   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016.     Нейрофизиологическое обоснование некоторой неврологической симтоматики острого периода черепно-мозговой травмы, обусловленной действием взрывной волны   В. А. Коршняк, А. И. Гоженко, Б. А. Насибуллин, Ю. В. Бовт, В. А. Жуков   Украинский НИИ медицины транспорта, Одесса Uniwersytet Kazimierza Wielkiego, Bydgoszcz Резюме             Авторы на основании результатов комплексного обследования 58 больных с ЗЧМТ, возникших в результате действия взрывной волны установили, что возникающий симтомокомплекс связан с нарушением деятельности корковых, стволовых и надсегментарных структур полушарий мозга. Авторы выявили, что тяжесть проявлений повреждения мозга связана с направленностью вектора действия взрывной волны. Наиболее выраженные изменеия отмечаются при сагиттальном, переднее-заднем действии вектора силы («в лицо»). Авторы полагают, что комплекс диэнцефально-стволовых и вестибулярных симптомов связан с гидродинамическим ударом ликвора желудочковой системы мозга на стволовые структуры и надсегментарные центры ЦНС. Ключевые слова: закрытая черепно-мозговая травма, взрывная волна, диэнцефальные центры центральной нервной системы. надсегментарные структуры вегетативной нервной системы.   Neurophysiological justification of some neurological symptoms of acute period of a craniocerebral injuries from an explosive WAVES   V. А. Коrshnyak, А. I. Gоzhеnkо, B. А. Nаsibullin, Uy. V. Bоwt, W. Zukow   Ukrainian Scientific and Research Institute of Transport Medicine, Odessa, Ukraine Kazimierz Wielki University, Bydgoszcz, Poland   Abstract Authors on the basis of the results of a comprehensive survey of 58 patients with traumatic brain injury, resulting from the action of the blast wave found that emerging simtomokompleks associated with impaired activity of cortical and stem structures suprasegmental brain hemispheres. The authors found that the severity of brain damage associated with the direction of action of the blast wave. The most pronounced Changes are marked with sagittal, anteroposterior action force vector ("face"). The authors suggest that the complex stem-diencephalic and vestibular symptoms associated with the hydrodynamic blow liquor ventricular system of the brain stem in the central nervous system structure and suprasegmental centers. Keywords: closed craniocerebral injury, blast, diencephalic centers of the central nervous system. suprasegmental structure of the autonomic nervous system.